(untitled) (Research, Society and Development, 2022)
The climatological water balance (CWB) is one of the ways to monitor water storage in the soil, being an essential tool in agricultural strategic planning. In this way, knowing the time of greater availability and the water deficit becomes important to assist in decision-making on agricultural planning in a given location. It contributes to the planning phase; new dams are built for water storage; irrigation systems are used at the most appropriate time to meet the crop and also allows the preservation of springs. In this context, two models were used to estimate the water balance: one proposed by Thornthwaite and Mather and another proposed by Rosa et al. Within the water balance, estimates can be made at river basin and rural property level, controlling the availability of water for the plants. Thus, the objective of this study was to address the main concepts regarding the study of water balance in different locations, basins, and physiographic regions.